Preterm Birth in Women With HIV: The Role of the Placenta - Ikumi, Nadia M.; Matjila, Mushi (Frontiers in Global Women's Health, 2022)
Maternal HIV infection is associated with an increased risk of preterm birth (PTB). However, the mechanisms underlying this increased risk in women with HIV remain poorly understood. In this regard, it is well-established that labor is an inflammatory process and premature activation of the pro-inflammatory signals (associated with labor) can result in preterm labor which can subsequently lead to PTB. HIV infection is known to cause severe immune dysregulation within its host characterized by altered immune profiles, chronic inflammation and eventually, the progressive failure of the immune system. The human placenta comprises different immune cell subsets, some of which play an important role during pregnancy including participating in the inflammatory processes that accompany labor. It is therefore plausible that HIV/antiretroviral therapy (ART)-associated immune dysregulation within the placental microenvironment may underlie the increased risk of PTB reported in women with HIV. Here, we review evidence from studies that point toward the placental origin of spontaneous PTB and discuss possible ways maternal HIV infection and/or ART could increase this risk. We focus on key cellular players in the maternal decidua including natural killer cells, CD4+ T cells including CD4+ regulatory T cells, CD8+ T cells as well as macrophages.